Ontogenetic distribution of Callinectes ornatus (Decapoda, Portunoidea) in southeastern Brazil - Andrade, Luciana Segura de [UNESP]; Fransozo, Vivian; Cobo, Valter Jose; Castilho, Antonio Leao [UNESP]; Bertini, Giovana [UNESP]; Fransozo, Adilson [UNESP] (Inst Investigaciones Oceanologicas, U A B C, 2013)
The spatial and seasonal distribution of different demographic groups of the swimming crab Callinectes ornatus was analyzed with respect to its population biology in three bays (Ubatumirim, Ubatuba, and Mar Virado) in southeastern Brazil. In each bay, monthly sampling was performed during two years along six transects, established at 5, 10, 15, and 20 m depth (parallel to the beach line), in a wave-sheltered area (7.5 m depth), and at an exposed site (10 m depth). Total abundance of crabs was similar among the bays. The presence of immature individuals, adult females, and breeding females was positively correlated with the bottom and surface temperatures, whereas adult males showed an opposite trend with respect to these factors. Immature and smaller individuals were most abundant along the sheltered and shallower transects. Males were more abundant along the shallower transects, and females at 15 and 20 m. This study revealed that different demographic groups occupy the habitat in different ways, according to local features. In general, southeastern Brazil offers a range of conditions that favor reproduction and consequently the maintenance and growth of the local population of C. ornatus, contributing to the relatively high abundance of the species in this coastal area.
Keywords: coastal monitoring; differential habitat occupation; ontogeny; predatory fishing; swimming crabs